Education on Diabetes Mellitus Prevention through Healthy Lifestyle among Adolescents at St. Pius Dormitory (YPK Don Bosco) Lubuk Pakam - Edarni Zebua; Salmi Angraini; Dian Novita; Joe Chresnando Ginting (JURNAL PENGMAS KESTRA (JPK), 2026)
Diabetes Mellitus is a non-communicable disease with an increasing prevalence among adolescents and is closely related to unhealthy lifestyles, such as high sugar consumption and low physical activity. This community service activity aimed to improve adolescents’ knowledge, attitudes, and commitment to diabetes mellitus prevention through the adoption of a healthy lifestyle. The activity was conducted in December 2025 at St. Pius Dormitory (YPK Don Bosco), Lubuk Pakam, using a descriptive qualitative approach with a cross-sectional design. A total of 24 male and female adolescents participated in the program. The intervention was carried out through health education, including interactive lectures, balanced nutrition education based on the “Isi Piringku” concept, practical simulations, group discussions, and educational quizzes. The results showed an improvement in adolescents’ knowledge, attitudes, and awareness after the education. Knowledge about diabetes mellitus increased from 29.2% before the intervention to 83.3% after the intervention. Awareness of the importance of physical activity increased from 37.5% to 85.4%, positive attitudes toward reducing sugar consumption increased from 34.6% to 81.3%, and commitment to adopting a healthy lifestyle increased from 29.2% to 79.2%. In conclusion, diabetes mellitus prevention education through a healthy lifestyle is effective in improving adolescents’ understanding and commitment and should be implemented continuously as an effort to prevent non-communicable diseases from an early age.